Rethinking China’s Rural Revitalization: The Development of a Sense of Community Scale for Chinese Traditional Villages - Wei Wang; Yun Gao; Adrian Pitts (Land, 2023)
Improving the sense of community (SOC) in Chinese traditional villages is crucial to preventing population loss and conserving the cultural heritage of China’s rural areas. These factors are important components of China’s rural revitalization policy, and thus, it is necessary to measure the SOC of villagers as part of the process. This study has developed a new SOC scale for Chinese traditional villages based on McMillan and Chavis’s four-factor theory involving membership, influence, need fulfillment, and emotional connections. An initial proposed sense of community scale for Chinese traditional village (SCSCTV) was structured as a four-factor scale with 28 items, including items from existing SOC studies and new items created by considering the features of Chinese traditional village communities. The scale was tested in the studies of three traditional villages in Chongqing by using two different methods. The findings provide guidance for the study of villages in the context of Chinese rural societies and a reliable scale for measuring villagers’ SOC.